Airborne Detection of H5N8 Highly Pathogenic Avian Influenza Virus Genome in Poultry Farms, France - Scoizec, Axelle; Niqueux, Eric; Thomas, Rodolphe; Daniel, Patrick; Schmitz, Audrey; Le Bouquin, Sophie (Frontiers in Veterinary Science, 2018)
In southwestern France, during the winter of 2016-2017, the rapid spread of highly pathogenic avian influenza H5N8 outbreaks despite the implementation of routine control measures, raised the question about the potential role of airborne transmission in viral spread. As a first step to investigate the plausibility of that transmission, air samples were collected inside, outside and downwind from infected duck and chicken facilities. H5 avian influenza virus RNA was detected in all samples collected inside poultry houses, at external exhaust fans and at 5 m distance from poultry houses. For three of the five flocks studied, in the sample collected at 50-110 m distance, viral genomic RNA was detected. The measured viral air concentrations ranged between 4.3 to 6.4 log10 RNA copies per m3, and their geometric mean decreased from external exhaust fans to the downwind measurement point. These findings are in accordance with the possibility of airborne transmission and question the procedures for outbreak depopulation.